Analysis of Disaster Preparedness among Regional Disaster Management Agency (RDMA) Officers Palu City - Napirah, Muhammad Ryman; Vidyanto; Asmawati (Universitas Mandala Waluya, 2023)
Preparedness according to Law Number 24 of 2007 Paragraph 7 is a series of activities carried out to anticipate disasters through appropriate and effective organization and action. Based on preliminary studies and initial interviews with employees at the Regional Disaster Management Agency (RDMA) Palu City, information was obtained that there were several problems in disaster preparedness, related to lack of attitude, emergency response plans, and resource mobilization. This research aims to determine the disaster preparedness of Palu City RDMA officers in the aspects of attitude, emergency response plans and resource mobilization. This research is qualitative research with a case study approach. The informants in this research were the Head of the Palu City RDMA as the key informant, the Palu City RDMA Secretary as the regular informant, and the Palu City RDMA staff as additional informants the sampling technique used was purposive sampling. The data in this research consists of primary data and secondary data. Data processing using matrix techniques where to ensure the validity of research results, technical triangulation was carried out as well as source triangulation. The results of research based on interviews supported by observation and documentation show that the attitudes, emergency response plans and resource mobilization of Palu City RDMA officers in disaster preparedness are good. So it can be concluded that disaster preparedness among Palu City RDMA officers is good. As a suggestion, it is hoped that the Palu City RDMA will increase awareness of disaster planning for officers.